Empowering Rural Communities through Appropriate Technology: A Case Study of Cattle Farming in West Bandung, Indonesia - Nengsih, Yanti Karmila; Sudiapermana, Elih; Wahyudin, Uyu; Pramudia, Joni Rahmat; Rasool, Shahid (Journal of Nonformal Education, 2026)
Background - Rural communities, particularly cattle farmers in Indonesia, often face challenges related to low productivity, economic vulnerability, and unsustainable agricultural practices. The integration of appropriate technology is posited as a critical driver for enhancing productivity and fostering sustainable livelihoods, yet its concrete impacts and implementation challenges in specific rural contexts like West Bandung require detailed investigation.Research Urgency -  There is a pressing need to identify effective strategies for rural community empowerment that can simultaneously boost economic outcomes and promote sustainable agriculture. While technology is often proposed as a solution, a significant gap exists in understanding its practical application, measurable impacts, and the real-world barriers to its adoption among smallholder cattle farmers in Indonesia.Research Method - This research employed a mixed-methods approach, combining quantitative surveys with qualitative interviews. Data was collected from cattle farmers in West Bandung Regency, West Java, to quantitatively measure changes in production and income, and qualitatively explore the experiences and challenges of technology adoption.Research Findings - The implementation of appropriate technology led to significant improvements: a 70% increase in milk production, a 40% increase in meat production, and a 40% rise in farmer income, alongside a 37.5% reduction in labor hours. However, major challenges were identified, including high initial costs, technical operational difficulties, and significant knowledge gaps among farmers.Research Conclusion - The study concludes that appropriate technology serves as a powerful catalyst for the economic empowerment and sustainable development of rural cattle farmers. For its transformative potential to be fully realized, the identified adoption barriers must be addressed through targeted strategies.Research Novelty/Contribution - This research provides a novel, empirically grounded demonstration of how context-specific technological interventions, when supported by a robust cooperative system, can create an integrated model for community empowerment. It offers a replicable framework for achieving sustainable agricultural development in similar rural contexts across Indonesia.